FENOLOGI PEMBUNGAAN Rhizophora mucronata Lamk. DI HUTAN MANGROVE PASURUAN, JAWA TIMUR (Flowering Fenology of Rhizophora mucronata Lamk. at Mangrove Forest Pasuruan, East Java) - Liliana Baskorowati; Subagya Subagya; Mohammad Mahmud; Mudji Susanto (Jurnal Penelitian Hutan Tanaman, 2018)
ABSTRACT Rhizophora mucronata Lamk. is a mangrove species developed for rehabilitation program along the north coast of Java Island. Increasing demand of propagules lead to the importance of gaining information regarding the flowers, fruits and propagules production within the area designated as seed source. Therefore, this research aimed to identify the flowers and propagules of R. mucronata production in the seed source area of Pesisir, Pasuruan, East Java. Flowering and fruiting phenology were observed by taking samples of trees to identify the development of the flowers and the propagules. Propagule production was observed by making a plot of 5 x 5 m, with the distance between plots measuring 100 m. Parameters of diameter, total height, and seed production were carried out on all trees in the plot. The results showed that R. mucronata bloomed throughout the observation period (January-April), with flowering that was not simultaneously in one tree. Reproductive cycle of this species took 15-16 months from bud commencement to propagule maturations; peak of flowering occurs from March to April and propagule production occurs on August. Propagules reach maturity and are ready for harvesting on December-January. Key word: Mangrove, Rhizophora mucronata, flowering, propagula  ABSTRAK Rhizophora mucronata Lamk. merupakan jenis tanaman mangrove yang dikembangkan untuk program rehabilitasi areal pantai utara Pulau Jawa. Informasi mengenai produksi propagula R. mucronata menjadi penting agar kebutuhan buah tercukupi. Penelitian ini ditujukan untuk mengetahui fenologi pembungaan dan pembuahan R. mucronata di areal sumber benih teridentifikasi Dusun Pesisir, Pasuruan, Jawa Timur. Fenologi pembungaan, pembuahan, dan produksi propagula diamati pada tiga sampel pohon per petak ukur. Produksi propagula diamati dengan membuat petak ukur 5 x 5 m, dengan jarak antar petak ukur 100 m; yang dibedakan antara petak ukur di tepi pantai dan di tepi daratan. Total petak ukur yang diamati ada sebanyak sepuluh petak ukur. Pengambilan data diameter, tinggi total dan produksi propagula dilakukan untuk semua pohon dalam petak ukur. Hasil penelitian menunjukkan bahwa R. mucronata berbunga selama pengamatan (Januari-April), dengan pembungaan yang tidak serempak dalam satu pohon. Siklus reproduksi memerlukan waktu 15-16 bulan mulai dari terbentuknya tunas sampai masaknya propagula; dengan puncak pembungaan terjadi pada bulan Maret-April dan musim berbuah pada bulan Agustus. Propagula mencapai tingkat masak siap dipanen pada bulan Desember-Januari.Kata kunci : Mangrove, Rhizophora mucronata, pembungaan, propagula